2007
DOI: 10.1038/sj.emboj.7601696
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium ParA/MinD-like VirC1 spatially coordinates early conjugative DNA transfer reactions

Abstract: Agrobacterium tumefaciens translocates T-DNA through a polar VirB/D4 type IV secretion (T4S) system. VirC1, a factor required for efficient T-DNA transfer, bears a deviant Walker A and other sequence motifs characteristic of ParA and MinD ATPases. Here, we show that VirC1 promotes conjugative T-DNA transfer by stimulating generation of multiple copies per cell of the T-DNA substrate (T-complex) through pairwise interactions with the processing factors VirD2 relaxase, VirC2, and VirD1. VirC1 also associates wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
124
3
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(133 citation statements)
references
References 48 publications
5
124
3
1
Order By: Relevance
“…In contrast, it is reported that VirD2 localizes at one pole in most of the cells in previous studies, in which the expression of FLAG-tagged VirD2 was under the virB promoter control (21). Our time-course study on GFP-VirD2 localization indicated that the discrepancy is likely due to the difference in gene expression levels.…”
Section: Discussioncontrasting
confidence: 50%
See 3 more Smart Citations
“…In contrast, it is reported that VirD2 localizes at one pole in most of the cells in previous studies, in which the expression of FLAG-tagged VirD2 was under the virB promoter control (21). Our time-course study on GFP-VirD2 localization indicated that the discrepancy is likely due to the difference in gene expression levels.…”
Section: Discussioncontrasting
confidence: 50%
“…In addition, the polar positioning of T-complex facilitated by VirC1 can be also helpful for the recruitment of T-complex to the T4SS apparatus (21). VirC1 antibody immunoprecipitated both T-strand and Ti-plasmid (21), suggesting that VirC1 binds to VirD2 during relaxosome assembly and remains bound during transit to the T4SS apparatus. On the other hand, VBP1 antibody immunoprecipitated only T-strand (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…VirC1 specifically binds to overdrive, and disruption of virC1 results in a loss of virulence similar to deletion of overdrive, suggesting that VirC1 functions through binding to overdrive (27,28). VirC1 belongs to the ParA/MinD ATPase superfamily containing a deviant Walker A box that is required for border nicking and for localizing the T-DNA to the cell pole (29,30). VirC1 also interacts with all other known T-DNA-processing proteins, including VirD1, VirD2, and VirC2, and thus it was proposed that VirC1 nucleates relaxosome assembly at T-DNA borders and spatially positions the T-DNA at the cell pole (29).…”
mentioning
confidence: 99%